Chronic kidney disease induced by an adenine rich diet upregulates integrin linked kinase (ILK) and its depletion prevents the disease progression - de Frutos, Sergio; Luengo, Alicia; García-Jérez, Andrea; Hatem-Vaquero, Marco; Griera, Mercedes; O'Valle, Francisco; Rodríguez–Puyol, Manuel; Rodríguez–Puyol, Diego; Calleros, Laura (Biochimica et biophysica acta. Molecular basis of disease, 2019)
Kidney fibrosis is one of the main pathological findings of progressive chronic kidney disease (CKD) although the pathogenesis of renal scar formation remains incompletely explained. Integrin-linked kinase (ILK), a major scaffold protein between the extracellular matrix (ECM) and intracellular signaling pathways, is involved in several pathophysiological processes during renal damage. However, ILK contribution in the CKD progress remains to be fully elucidated. In the present work, we studied 1) the renal functional and structural consequences of CKD genesis and progression when ILK is depleted and 2) the potential of ILK depletion as a therapeutic approach to delay CKD progression. We induced an experimental CKD model, based on an adenine-supplemented diet on adult wild-type (WT) and ILK-depleted mice, with a tubulointerstitial damage profile resembling that is observed in human CKD. The adenine diet induced in WT mice a progressive increase in plasma creatinine and urea concentrations. In the renal cortex it was also observed tubular damage, interstitial fibrosis and progressive increased ECM components, pro-inflammatory and chemo-attractant cytokines, EMT markers and TGF-β1 expressions. These observations were highly correlated to a simultaneous increase of ILK expression and activity. In adenine-fed transgenic ILK-depleted mice, all these changes were prevented. Additionally, we evaluated the potential role of ILK depletion to be applied after the disease induction, as an effective approach to interventions in human CKD subjects. In this scenario, two weeks after the establishment of adenine-induced CKD, ILK was abrogated in WT mice and stabilized renal damage, avoiding CKD progression. We propose ILK to be a potential target to delay renal disease progression. •The adenine-induced mouse model of CKD shows increased ILK expression and activity.•ILK depletion prevents the structural and functional progression of induced CKD.•ILK depletion provides mechanisms to protect against fibrosis, EMT and Inflammation.•After CKD has started ILK abrogation stabilized and avoided progression to end-stage.•This emphasizes the potential application of ILK blockade in clinical practice.